Consumer Perceptions Towards Organic Food (International Journal of Innovative Research in Computer Science & Technology, 2022)
Consumer Food security, personal  wellness, and ecological issues, as well as sensual aspects  like nutritious value, flavor, cleanliness, and beauty, all  impact natural agricultural choices. While ethnic  considerations may aid in the identification of organic  clients, the link isn't very strong. Customers link organic  food with organic procedures, ecological and livestock  health, and the lack of pesticides and fertilizers. High costs  continues to restrict organic product use. Knowing the  elements that influence natural foods intake, such as  motivations, is critical to assessing if clean product has the  capacity to become a truly mainstream market.  Agricultural security, human wellness, and environmental  issues, as well as senses aspects such as nutritious value,  flavor, fresh, and beauty, all affect customer preference for  organic foods. While demographic considerations may aid  in the identification of organic clients, the link isn't very  strong. Consumers link organic food with organic  procedures, environmentalist and animal health, and the  lack of herbicides and fertilizers. High costs continue to  restrict organic food use. Understanding the elements that  influence natural product intake, such as desire, is  important, is important to determining if organic food has  the potential to become a true mainstream industry.
Keywords: Agriculture; Consumer Attitude; Consumer Perception; Organic Food; Purchase Intention